Power and International relations: Essays in Honour of Coral Bell - Ball, Desmond (ANU Press, 2014)
Coral Mary Bell AO, who died in 2012, was one of the world's foremost academic experts on international relations, crisis management and alliance diplomacy. This collection of essays by more than a dozen of her friends and colleagues is intended to honour her life and examine her ideas and, through them, her legacy.